Diffuse intrinsic pontine glioma: poised for progress - Warren, Katherine (Frontiers in Oncology, 2012)
Diffuse intrinsic pontine gliomas (DIPGs) are amongst the most challenging tumors to treat. Surgery is not an option, the effects of radiation therapy are temporary, and no chemotherapeutic agent has demonstrated significant efficacy. Numerous clinical trials of new agents and novel therapeutic approaches have been performed over the course of several decades in efforts to improve the outcome of children with DIPG, yet without success. The diagnosis of DIPG is based on radiographic findings in the setting of a typical clinical presentation, and tissue is not routinely obtained as the standard of care. The paradigm for treating children with these tumors has been based on that for supratentorial high-grade gliomas in adults as the biology of these lesions were presumed to be similar. However, recent pivotal studies demonstrate that DIPGs appear to be their own entity. Simply identifying this fact releases a number of constraints and opens opportunities for biologic investigation of these lesions, setting the stage to move forward in identifying DIPG-specific treatments. This review will summarize the current state of knowledge of DIPG, discuss obstacles to therapy, and summarize results of recent biologic studies.